Polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in Antarctic ice-free areas: Influence of local sources on lakes and soils - VECCHIATO, MARCO; ZAMBON, STEFANO; ARGIRIADIS, ELENA; BARBANTE, Carlo; GAMBARO, Andrea; PIAZZA, Rossano (Microchemical Journal, 2015)
Antarctica is usually considered a pristine ecosystem; nevertheless it is influenced by Persistent Organic Pollutants (POPs),mainly driven by long-range atmospheric transport (LRAT). However, localized sources such as human and wildlife activities can also contribute to pollution, constituting contaminated points at a local scale. Antarctic ice-free areas, where rare lakes are located, are influenced by such sources. In this work we determine polychlorinated biphenyls (PCBs, including the non-Aroclor CB-11) and polybrominated diphenyl ethers (PBDEs) in water and sediment samples of 6 lakes in Northern Victoria Land and in soils near the Italian research station Mario Zucchelli. Determinations were performed through gas chromatography (GC) coupled both to low-resolution and highresolution mass spectrometry (LRMS, HRMS). POP concentrations in lakes resulted low and rather similar across the sites despite their distance: ΣPCBs range between 46 and 143 pg L−1 in water and 10 and 634 pg g−1 in sediments, while ΣPBDEs range between 60 and 151 pg L−1 in water and 193 and 1682 pg g−1 in sediments. Lakes exhibited limited amplification phenomena in water during the melting season. PBDEs in the soils near the base yielded more concerning results, reaching a concentration of 33 ng g−1. Antarctica is usually considered a pristine ecosystem; nevertheless it is influenced by Persistent Organic Pollutants (POPs), mainly driven by long-range atmospheric transport (LRAT). However, localized sources such as human and wildlife activities can also contribute to pollution, constituting contaminated points at a local scale. Antarctic ice-free areas, where rare lakes are located, are influenced by such sources. In this work we determine polychlorinated biphenyls (PCBs, including the non-Aroclor CB-11) and polybrominated diphenyl ethers (PBDEs) in water and sediment samples of 6 lakes in Northern Victoria Land and in soils near the Italian research station Mario Zucchelli. Determinations were performed through gas chromatography (GC) ...